2020
DOI: 10.1111/ejh.13476
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and thalassaemia: A position statement of the Thalassaemia International Federation

Abstract: Objectives Many patients with haemoglobinopathies, including thalassaemia and sickle cell disease, are at increased risk of developing severe complications from the coronavirus disease 2019 (COVID‐19). Although epidemiologic evidence concerning the novel coronavirus (SARS‐CoV‐2) infection in these patients is currently lacking, the COVID‐19 pandemic represents a significant challenge for haemoglobinopathy patients, their families and their attending physicians. Methods The present statement summarizes the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…The presence of comorbidities associated with age, 3 , 4 , 38 as well as the known long-term complications inherent to hemoglobinopathies, may contribute to the increased mortality out of the pediatric age group bracket. 39 , 40 The clinical course of COVID-19 in pediatric patients has been favorable, but data on children and adolescents with chronic diseases are still scarce. 41 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of comorbidities associated with age, 3 , 4 , 38 as well as the known long-term complications inherent to hemoglobinopathies, may contribute to the increased mortality out of the pediatric age group bracket. 39 , 40 The clinical course of COVID-19 in pediatric patients has been favorable, but data on children and adolescents with chronic diseases are still scarce. 41 …”
Section: Discussionmentioning
confidence: 99%
“…reported that the COVID-19 pandemic represents a significant challenge for haemoglobinopathy patients, their families and their attending physicians. They present a statement who summarizes the key challenges concerning the management of haemoglobinopathies, with particular focus on patients with either transfusion-dependent or non-transfusion-dependent thalassaemia [ 10 ]. They illustrate that adaptation of thalassaemia care during the present and potential future similar pandemics requires on one hand the strengthening of existing and creation of new communication channels between healthcare professionals and patients and on the other the promotion of a modified patient pathway for access to care including visits to medical facilities [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the clinical effects of sickle cell disease and alpha-thalassemia trait (or alpha-thalassemia disease) are not clear [ 22 ]. The effects of alpha-thalassemia on susceptibility to severe COVID-19 infection are unknown [ 23 ]. In addition, HbSC disease is milder than HbSS disease including lower rates of ACS [ 24 , 25 ] although HbSC patients may be at particular risk for fat embolism syndrome [ 26 ].…”
Section: Discussionmentioning
confidence: 99%